2011
DOI: 10.1590/s0365-05962011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico-epidemiológico das doenças sexualmente transmissíveis em crianças atendidas em um centro de referência na cidade de Manaus, Amazonas, Brasil

Abstract: FUNDAMENTOS: Doenças Sexualmente Transmissíveis em crianças permanecem um problema de saúde pública pouco estudado, sendo ainda necessários esclarecimentos sobre seu manejo e a relação destas com o abuso sexual infantil. OBJETIVOS: Descrever o perfil clínico-epidemiológico das Doenças Sexualmente Transmissíveis em crianças atendidas em centro de referência na cidade de Manaus. MÉTODOS: Realizou-se estudo descritivo exploratório para verificar características clínicas, epidemiológicas e laboratoriais das Doença… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(40 reference statements)
0
3
0
1
Order By: Relevance
“…The studies included 103,965 participants, of whom 36,304 were males and 55,674 females (4898 pregnant). Age ranged from 0 years (< 3 month) [ 50 ] to 93 years [ 59 ], with mean age between 8.5 years [ 115 ] and 54 years [ 59 ] and median age between 7.9 years [ 113 ] and 45 years [ 95 ]. The reported female-to-male ratio was 1.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included 103,965 participants, of whom 36,304 were males and 55,674 females (4898 pregnant). Age ranged from 0 years (< 3 month) [ 50 ] to 93 years [ 59 ], with mean age between 8.5 years [ 115 ] and 54 years [ 59 ] and median age between 7.9 years [ 113 ] and 45 years [ 95 ]. The reported female-to-male ratio was 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…Co-infections were common: 42.9% with herpes simplex virus (HSV) [ 48 ], 0.8% [ 103 ] to 100% [ 63 , 82 , 103 ] with Chlamydia trachomatis , 5.6% [ 140 ] to 100% [ 117 ] with human papillomavirus (HPV), 7.1% [ 48 ] to 20% [ 73 , 117 ] with syphilis, 15.7% [ 115 ] to 50% [ 38 ] with Trichomonas vaginalis , 10.5% with concomitant bacterial vaginosis [ 115 ], 11.1% [ 118 ] to 21.4% [ 48 ] with Mycoplasma genitalium , 100% with Mycoplasma hominis [ 98 ], 75.3% with Ureaplasma urealyticum / parvum and 2.8% with hepatitis C virus [ 140 ]. One study reported 81.5% of co-infections with more than one microorganism ( M. genitalium , M. hominis , Gardnerella vaginalis and T. vaginalis ) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 Two years later, another study indicated that a large part of the population was asymptomatic, requiring STI tracing in nonclinical settings 7 , which is not different from the present days. Knowledge and attitudes towards STIs are highlighted in many studies in different age groups.…”
mentioning
confidence: 87%
“…O diagnóstico precoce apropriado é crítico quando exposto a uma infecção sexualmente transmissível em um menor, então é realizado uma investigação de como a doença se espalha para avaliar a probabilidade de abuso sexual, e é de suma importância que os dentistas compreendem a importância das doenças infecciosas estando sempre atento a essas manifestações (Ribas et al, 2011).…”
Section: Infecções Sexualmente Transmissíveisunclassified